Strategi Manajerial dalam Meningkatkan Daya Saing UMKM di Era Digital - Etty Zuliawati Zed; Salsabila Al Muniroh; Asmala Sabrina; Novitasari; Adel Paila (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine managerial strategies implemented by MSMEs (Micro, Small, and Medium Enterprises) to enhance their competitiveness in the digital era using a qualitative method. MSMEs face significant challenges in maintaining their existence and expanding their market amid rapid technological advancements. Through in-depth interviews and observations with MSME actors, this research explores how digital transformation, digital marketing strategies, and digital capability development are managed managerially to improve operational effectiveness and broaden market reach. The results indicate that the application of digital management, including the utilization of social media, e-commerce, and management information systems, can increase brand awareness, customer loyalty, and business efficiency. Furthermore, the development of digital skills among human resources is a key factor in the successful digital transformation that positively impacts MSMEs’ competitiveness in local markets. This study provides recommendations for MSME practitioners and stakeholders to comprehensively integrate digital strategies to face competition in the digital era.